"All things must pass" - Cutaneous migration of an endobronchial valve. Issue 1 (January 2022) - Lee, Michelle; Baranowski, Ralitsa; Gammon, David; Hargrave, Joanne; Waller, David
Summary: The Zephyr (PulmonX Inc., Redwood, CA) endobronchial valve (EBV), predominantly designed for lung volume reduction in emphysema, can also be used to close a spontaneous or post-operative prolonged air leak (PAL). We describe a previously unreported complication of cutaneous migration of an EBV, inserted for management of a PAL from a postoperative bronchopleural fistula (BPF), in a 62-year-old male following a right upper lobe posterior-apical (S1, 2) segmentectomy. His PAL resulted in a chronic empyema which failed to respond to surgical debridement, anterior cavernostomy and pectoral myoplasty. Bronchoscopic closure of the air leak by EBV insertion resulted in clinical improvement but there was a residual chronic wound sinus through which the patient reported protrusion of a foreign body that was causing irritation. It was the EBV. We hypothesise that the BPF healed beneath the EBV causing it to dislodge but its route to the skin remains a mystery.